Efficacy and safety of Maternal voice for Preterm Neonatal Pain: a Systematic Literature Review - Mastuti, Ni Luh Putu Herli (Universitas Andalas, 2023)
Purpose: Pain in neonates, especially in preterm neonates has short effects and long effects. A motherâ€™s voice can stabilize the physiological state, support feeding, reduce pain, and promote growth and development. aimed to analyze the effect and safety of maternal voice for preterm neonatal pain, to provide scientific evidence.Design : The research design used in this study is the systematic literature review. The identification of the study uses a PRISMA flow diagram, and quality assessment uses critical appraisal tools from the Centre for Evidence-Based Medicine. The analyzed data related to the population, intervention, and outcomes (PIO components).Findings: Ten studies were included in this study, ranging from 2018 to 2023. Seven studies showed the significant efficacy of maternal voice in reducing preterm neonatal pain, and three studies no significance. Five studies show maternal voice can reduce pain significantly more than routine care, and two studies use a combination of maternal voice and other non-pharmacological management, including breast milk, taste, Non-nutritive sucking, heartbeat sounds mother voice, and mother touch therapy. Pain parameters use the Pain Scale and serum and salivary cortisol level.Implications: Maternal voice; both live or recorded, voice or heartbeat, was effective and safe in reducing pain sensation in preterm neonates.Â